TI_GERICHTE 52.2004.326 vom 10. Mai 2006 , Ristrutturazione ed ampliamento di un rustico formato da due corpi contigui - TI Tribunale d'appello (2006)
Ristrutturazione ed ampliamento di un rustico formato da due corpi contigui